A comparative study of five regression testing algorithms - Mansour, N. (1997)
We compare five regression testing algorithms that include: slicing, incremental, firewall, genetic and simulated annealing algorithms. The comparison is based on the following ten quantitative and qualitative criteria: execution time, number of selected retests, precision, inclusiveness, user parameters, handling of global variables, type of maintenance, type of testing, level of testing, and type of approach. The experimental results show that the five algorithms are suitable for different requirements of regression testing. Nevertheless, the incremental algorithm shows more favorable properties than the others.